English Auctions and Walrasian Equilibria with Multiple Objects: a dynamic approach - Jinpeng Ma (Rutgers University, Department of Economics, 1997)
This paper studies the English (progressive) auction for an exchange economy with multiple objects. The English auction is a tatonnement process and lasts multiple rounds. It is modeled as a sequence of round games. Each round game is a normal form game in which an agent's strategies are his bids and his payoff is his trading profits of his winning bundle at that round. Among all these normal form games, all intermediary round games are in fact the ''virtual'' games because the payoffs to agents are not finalized unless the auction closes. We show that any ascending price sequence obtained from the English auction converges to a Walrasian equilibrium (if any) within finite rounds when agents submit their bids that consist of a Nash equilibrium in each round game. We also provide a sufficient condition for the English auction to converge to a Walrasian equilibrium in finite rounds. But this condition is weaker than the Nash equilibrium. This shows that the Nash equilibrium is not necessary (though sufficient) for the English auction to converge to a Walrasian equilibrium.
Keywords: D41; 330; Exchange economy with multiple objects